Proposed business strategy for “travorama for business” in business to business market - Angga Putra, Raymond; Aditya Wibowo, Satya (The Indonesian Journal of Business Administration, 2018)
Abstract - As a service company, Applus Velosi introduces a new method for the inspection of offshore platform by using (Unmanned Aerial Vehicle) UAV. The company need to conduct financial feasibility study to determine the rate for the service. The research uses both qualitative and quantitative method. Qualitative data obtained through interview of staff and top management of the company, while quantitative data through company’s financial data and historical data. The objective of this research is to evaluate the financial feasibility of the project of aerial inspection facility for offshore platform in Indonesia. The research will be anaylzed based on PESTEL Analysis, Business Model Canvas, CVP analysis and financial feasibility analysis which includes break-even analysis, payback period, ROI, NPV, IRR, PI, and WACC. The project’s tolerance will be analyzed by using sensitivity analysis. This research limitation is only focused on offshore platform of oil and gas industry in Indonesia. The research finding shows that the project of aerial inspection facility for offshore platform in Indonesia is financially feasible using $800 as base service rate. The project has positive NPV and IRR is higher than WACC, profitability index is greater than 1, and payback period is around 1 year. Keywords: CVP Analysis, Financial Feasibility Study, Offshore Platform, Sensitivity Analysis, UAV